(untitled) (Journal of Hama University, 2026)
The research aimed to identify the role of the physical school environment in improving the functional performance level of school principals from the teachers’ perspective in Lattakia city, and to identify the differences in the role of the physical school environment in improving the functional performance level of principals from the teachers’ perspective according to the two variables (years of experience, academic qualification). The descriptive method was used, and to achieve the research goal, a questionnaire consisting of (46) items was designed and applied to a sample of (196) male and female teachers from public secondary schools in Lattakia city. The research results indicated that the role of the physical school environment in improving the functional performance of managers, from the teachers’ perspective in Lattakia city , was moderate. The results also showed no statistically significant differences between the average scores of teachers on the questionnaire regarding the role of the physical environment in developing the functional performance of managers in public secondary schools in Latakia, depending on the variable of years of experience, and there were statistically significant differences between the average scores of teachers on the questionnaire regarding the role of the physical environment in developing the functional performance of managers in public secondary schools in Latakia, depending on the variable of academic qualification, in favor of those with higher qualifications.